Investigating the effect of Glomus etunicatum colonization on structure and phloem transport in roots of Eragrostis curvula (Umgeni) - Skinner, Amy (Rhodes University, Faculty of Science, Botany Department, 2007)
The symbiotic unit of an arbuscular mycorrhizal fungus and its host is able toachieve and maintain far higher inflow of nutrients than non-mycorrhizal roots. The colonization strategy of the mycobiont within the plant is intrinsic to the symbiosis with respect to both structural adaptations and nutrient exchange. An investigation into the effect of Glomus etunicatum colonization on the structure and phloem transport in Eragrostis curvula (Umgeni) allowed for greater insight into the dynamic of the symbiosis. The combined use of stains (such as Trypan Blue, Chlorazol Black, Safranin and Fast Green), and techniques, (such as freeze-microtome transverse sectioning and permanent slide preparations) contributed to a successful general observation of an intermediate colonization strategy using light microscopy methods. However, clarity into structural detail of mycorrhizal forms required electron microscopy studies. The SEM method used with freeze fracture was a relatively quick and simple method allowing for the observation of surface and internal features. The TEM method allowed for highresolution images providing insight into the variations in the apoplasmic compartmental form, and how this may relate to the function of the symbiosis with regard to fungal coils or arbuscules. The apoplasmic nature of mycorrhizas was substantiated and no symplasmic connections were found between symbionts. Fluorescence studies demonstrated that 5,6-carboxyfluorescein was transported through the phloem into the roots of E. curvula, but remained predominantly in the root phloem. Unloading only occurred in optimal nutrient exchange areas of meristimatic lateral or apical growth regions. It was not possible, using fluorescence techniques and related equipment available, to conclusively establish if there were symplasmic connections between the mycobiont and its host or if bidirectional transfer of nutrients occurred at the same interface.
Keywords: Glomus (Fungi); Phloem; Plant translocation; Weeping lovegrass; Vesicular-arbuscular mycorrhizas; Mycorrhizal fungi; Mycorrhizas